Elektroda Pasta Karbon yang Dimodifikasi dengan Molecularly Imprinted Polyaminophenol untuk Analisis Parasetamol secara Voltammetri - Michelle
Acetominophen is known as paracetamol, a medicine to reduce pain (analgesic) and fever (antipyretic). However, overdoses of paracetamol can cause liver failure. In this study, analysis of paracetamol was conducted using voltammetric method. In this research, working electrode used was a carbon paste electrode modified with Molecularly Imprinted Polymers (MIP) made from 3-aminophenol as monomer and paracetamol as template. Electropolimerization was conducted using cyclic voltammetric technique in the potential range of -0.2 V - 1.2 V and scan rate of 100 mV/s. Linear calibration curve was obtained in the concentration range of 0.001 mM - 0.1 mM with a detection limit of 0.543 ?M. Analysis of five commercial drug samples showed that the developed voltammetric method gave better results than the spectrophotometric method.